2018
DOI: 10.1177/0255761418763914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of accurate and inaccurate visual feedback on the tuning accuracy of high school and college trombonists

Abstract: We examined how visual feedback from electronic tuners affected trombonists’ pitch performance and tuning confidence. High school ( n = 29) and college trombonists ( n = 30) were tasked to play in tune with a stimulus tone (G3) recorded by a professional trombonist presented through headphones. Following each of three attempts, participants rated their confidence level that their performance was in tune. A different tuner was provided during each tuning attempt and set to one of three conditions: in-tune (A = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
(60 reference statements)
3
13
1
Order By: Relevance
“…In contrast with most part of the previous research that has studied the use of technology to provide different kinds of feedback to improve learning (Thorpe, 2002; Welch et al, 2004; Wilson et al, 2008; Van Der Linden et al, 2011; Wang et al, 2012; Leong and Cheng, 2014; Schlegel and Gregory Springer, 2018), we did not found statistical differences between the amount of improvement at the end of the task between the BF and the BNF group. However, behavioral differences found among the BF group could be the result of an increment of the conscious awareness of their own performance as suggested by Hamond (2017).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast with most part of the previous research that has studied the use of technology to provide different kinds of feedback to improve learning (Thorpe, 2002; Welch et al, 2004; Wilson et al, 2008; Van Der Linden et al, 2011; Wang et al, 2012; Leong and Cheng, 2014; Schlegel and Gregory Springer, 2018), we did not found statistical differences between the amount of improvement at the end of the task between the BF and the BNF group. However, behavioral differences found among the BF group could be the result of an increment of the conscious awareness of their own performance as suggested by Hamond (2017).…”
Section: Discussionmentioning
confidence: 93%
“…The study reported improved pitch accuracy by using the system. Previous research has studied the effect of using different kinds of interfaces and different kinds of feedback in singing voice (Thorpe, 2002; Welch et al, 2004; Wilson et al, 2008; Leong and Cheng, 2014), trombone (Schlegel and Gregory Springer, 2018), piano (Hamond, 2017), and violin (Wang et al, 2012). Although there are differences in the way RTVF may improve performance, most of the previous studies reported beneficial effects of RTVF in learning.…”
Section: Introductionmentioning
confidence: 99%
“…Results suggested a minimum sample size of 54 (input parameters included Pillai’s criterion = .6, an alpha level of .05, and a power level [1 – β] of .8). We selected these input parameters based on a review of Cohen’s (1998) power guidelines as well as effect sizes reported in previous research focused on pitch and timbre performance (e.g., Byo et al, 2011; Schlegel & Springer, 2018). Participants ( N = 56) were high school trumpeters from three successful high school band programs in the southeastern United States (as evidenced by their regular superior ratings at adjudicated performance assessments and the number of students who participated in honor bands) and collegiate trumpeters from two large schools of music in the southeastern United States accredited by the National Association of Schools of Music.…”
Section: Methodsmentioning
confidence: 99%
“…Results of that study (Schlegel & Springer, 2018) indicated that those musicians’ pitch accuracy was swayed by the visual feedback provided by the tuner, even when that feedback was incorrect by a large deviation of 11.8 cents. Band directors should be aware of this potential tendency and use tuners judiciously with that in mind.…”
Section: Chromatic Tunersmentioning
confidence: 99%
“…One of the criticisms of tuners has been that they can unintentionally cause students to rely on visual information over aural information when focusing on intonation (Feldman et al, 2016). Schlegel and Springer (2018) conducted a study where high school and collegiate trombonists were asked to match pitch with a recording of a professional trombonist performing a sustained G pitch (fourth space, bass clef). They completed this tuning task several times, but during each attempt, they viewed a different tuner.…”
Section: Chromatic Tunersmentioning
confidence: 99%